EU enlargement and the portuguese economy - Barry, Frank (2010)
Ten states, primarily from Central and Eastern Europe, will be admitted to the EU in 2004. The present paper assesses the competitiveness implications of this enlargement for Portugal. Four specific topics are considered: the trade and industry effects, the implications for Portugal's ability to attract FDI, the likely levels and consequences of immigration from Central and Eastern Europe and the implications for Portugal's budgetary relations with the rest of the EU.